Paciente de sexo femenino de 69 años de edad con parkinson. - Izurieta Ambi, Lizbeth Elvia (2021)
The present clinical case is of a 69-year-old female patient with Parkinson's who came to the medical consultation for presenting sporadic movements of the upper extremities, difficulty speaking, difficulty eating correctly, swallowing food, and weight loss. A nutritional care process was carried out in order to maintain a good nutritional status of the patient. Anthropometric, biochemical, clinical and dietary indicators were used which showed us a deficient protein-energy intake (NI-5.3), related to difficulty in eating correctly and swallowing food, evidenced by weight loss; and the 24-hour recall showed a hypocaloric and hypoprotein diet. For this reason, in the present clinical case, a dietary plan adapted to the pathological condition was proposed and an adapted basic diet (ABA) of 2,200 hyperprotein calories with protein redistribution, divided into 6 meal times, moderate volume, warm temperature and smooth consistency was prescribed. As a result, it was possible to maintain control of the dietary plan and follow-up of the patient, beneficial responses were evidenced in the nutritional status of the patient with Parkinson's disease, such as an increase in body weight of 3kg, an increase in body mass index was observed reflecting an increase of lean mass and lean mass, improved the protein profile in the laboratory values of albumin and total proteins with data in the minimum range of normal, improved his texture in relation to weight gain and tolerance and adherence to the diet.